Mapping the Minds of Retirement Planners - Douglas A. Hershey; Kène Henkens; Hendrik P. van Dalen (Tinbergen Institute, 2006)
This study explored the psychological mechanisms that underlie the retirement planning and saving tendencies of Dutch and American workers. Participants were 988 Dutch and 429 Americans, 25-64 years of age. Analyses were designed to: (a) examine the extent to which structural variables were related to planning tendencies, and (b) develop culture-specific path analysis models to identify the mechanisms that underlie perceived financial preparedness for retirement. Findings revealed striking differences across the Netherlands and the United States not only among structural variables predictive of key psychological and retirement planning constructs, but also in the robustness of the path models. These findings suggest that policy analysts should take into account both individual and cultural differences in the psychological predispositions of workers when considering pension reforms that stress individual responsibility for planning and saving.
Keywords: D14; D91; J26; P52; 330; retirement; pensions; financial planning; psychology; saving; uncertainty